Tantangan dan Inovasi: Evaluasi Pendidikan Masa Depan - Sinuraya, Ananda Mardianus; Asbari, Masduki; Angin, Sharon Hillary Br Perangin (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to encourage improvement in order to have better abilities, awareness, skills and quality of life in general. This study uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from the Satu Youtube channel Percent entitled